UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI SISTEM REPRODUKSI MANUSIA DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH - Dita Putri Iskandar Nasution (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Abstract: This study aims to determine the increase in activity and student learning outcomes by using problem-based learning model (PBM) on human reproduction system materials in class XI IPA1 SMA Swasta IT Indah Medan Learning Year 2020/2021. This type of research is a classroom action research. Subject of this research is class XI IPA1 SMA IT Indah Medan with the number of students is 33. Based on the results of data analysis, it is known that there is an increase of activity and student learning outcomes in each cycle, for the data of student learning activity is known that the level of student learning activity cycle I first meeting is quite bad, in cycle I second meeting pertained enough, in cycle II increase student activity pertained good. For data of learning result at pretest the percentage of student acquisition is 0% which is very low, increasing at posttest (cycle I) to 23% which is still low and increasing again at postest (cycle II) to 89,74% which is high. For percentage of achievement data Indicator known that in the first cycle of learning objectives set on both indicators have not been achieved, whereas in cycle II the indicator set has been achieved. Keywords: problem based learning, student learning activity, student  learning outcomes. Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan aktivitas dan hasil belajar siswa dengan menggunakan model pembelajaran berbasis masalah (PBM) pada materi sistem reproduksi manusia di kelas XI IPA1 SMA Swasta IT Indah Medan Tahun Pembelajaran 2020/2021. Jenis penelitian ini adalah penelitian tindakan kelas. Subjek penelitian ini adalah kelas XI IPA1 dengan jumlah siswa 33 orang. Berdasarkan hasil analisis data diketahui bahwa ada peningkatan aktivitas dan hasil belajar siswa pada tiap siklus, untuk data aktivitas belajar siswa diketahui bahwa tingkat aktivitas belajar siswa siklus I pertemuan pertama tergolong buruk, pada siklus I pertemuan kedua tergolong cukup, pada siklus II peningkatan aktivitas siswa tergolong baik. Untuk data hasil belajar saat pretest persentase perolehan siswa adalah sebesar 0% yang tergolong sangat rendah, meningkat pada postest (siklus I) menjadi 23% yang tergolong masih rendah dan kembali meningkat saat postest (siklus II) menjadi 89,74% yang tergolong tinggi. Untuk data persentase ketercapaian Indikator diketahui bahwa pada siklus I tujuan pembelajaran yang ditetapkan pada kedua indikator belum tercapai, sedangkan pada siklus II indikator yang ditetapkan telah tercapai. Kata kunci: model pembelajaran berbasis masalah, aktivitas belajar siswa, hasil belajar siswa.